Building University Brand Equity Through Service and Symbolic Attributes: The Mediating Role of Brand Image - Tri Lestira Putri Warganegara; M. Yusuf Sulfarano Barusman; Andala Rama Putra Barusman; Habibburahman (Fundamental and Applied Management Journal, 2026)
Increasing competition in higher education has compelled private universities to strengthen their institutional brands to attract prospective students, enhance stakeholder confidence, and sustain long-term competitiveness. Because higher education is a credence service, prospective students are generally unable to evaluate educational quality before enrollment and therefore tend to rely on institutional reputation when making their decisions. Therefore, understanding the factors that shape university brand equity has become increasingly important. Although previous studies have examined service attributes and symbolic attributes separately, limited research has investigated their combined effects on university brand equity through brand image, particularly in private universities in developing countries. Therefore, using brand image as a mediating factor, this study investigates how service attributes and symbolic attributes affect university brand equity. Using survey data gathered from 394 students enrolled in seven private universities in Bandar Lampung, Indonesia, a quantitative technique was used. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both the direct and indirect relationships among the proposed constructs. The findings indicate that service attributes do not have a significant direct effect on brand equity. In contrast, symbolic attributes have a positive and significant effect on brand equity. Furthermore, both service attributes and symbolic attributes positively influence brand image, which in turn has a positive and significant effect on brand equity. Additionally, the mediation study shows that while brand image somewhat mediates the association between symbolic traits and brand equity, it entirely mediates the correlation between service attributes and brand equity. These findings demonstrate that students’ perceptions of institutional image play a critical role in translating both service attributes and symbolic attributes into university brand equity. By integrating symbolic and service attributes into a single model to describe how university brand equity is formed through brand image, this study adds to the body of knowledge on university branding. The findings suggest that private universities should strengthen not only service quality but also symbolic attributes, including institutional reputation, prestige, and identity, to build a stronger brand image and enhance university brand equity. This study is limited to student respondents from private universities within a single geographical region, which may restrict the generalizability of the findings.